2003
DOI: 10.1210/en.2002-0136
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Differences from the A and B Isoforms of the Insulin Receptor (IR) in 32D Cells in the Presence or Absence of IR Substrate-1

Abstract: The A isoform of the insulin receptor (IR) is frequently overexpressed in cancer cells and is activated by IGF-II as well as by insulin, whereas the B isoform is predominant in differentiated tissues and responds poorly to IGF-II. The IR substrate-1 (IRS-1), a docking protein for the IR, is known to send a mitogenic signal and to be a powerful inhibitor of cell differentiation. We have investigated the biological effects of the two IR isoforms in parental 32D hemopoietic cells, which do not express IRS-1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 68 publications
1
69
0
Order By: Relevance
“…Lower panel: The abundance of pS2 and 36B4 mRNAs in COS-7 cells transfected with different plasmids was detected by RT-PCR, as described in Materials and methods Nuclear IRS-1/ERa interactions C Morelli et al tion of IRS-1 is blocked with ICI and does not occur in ERa-negative cells; (3) nuclear IRS-1 interacts with ERa; (4) nuclear IRS-1 is corecruited with ERa to the ERE-containing pS2 promoter; and (5) the presence of IRS-1 decreases ERa transcription at ERE promoters. Nuclear localization of IRS-1 has recently been described in different cellular systems (Lassak et al, 2002;Prisco et al, 2002;Sun et al, 2003;Tu et al, 2002;Sciacca et al, 2003). The mechanism by which IRS-1 enters cell nucleus is still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower panel: The abundance of pS2 and 36B4 mRNAs in COS-7 cells transfected with different plasmids was detected by RT-PCR, as described in Materials and methods Nuclear IRS-1/ERa interactions C Morelli et al tion of IRS-1 is blocked with ICI and does not occur in ERa-negative cells; (3) nuclear IRS-1 interacts with ERa; (4) nuclear IRS-1 is corecruited with ERa to the ERE-containing pS2 promoter; and (5) the presence of IRS-1 decreases ERa transcription at ERE promoters. Nuclear localization of IRS-1 has recently been described in different cellular systems (Lassak et al, 2002;Prisco et al, 2002;Sun et al, 2003;Tu et al, 2002;Sciacca et al, 2003). The mechanism by which IRS-1 enters cell nucleus is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several rigorously controlled studies demonstrated that nuclear IRS-1 can be found in cells transformed by oncogenic proteins, for example, T antigens of the JCV (Lassak et al, 2002) and SV40 viruses, and v-src (Tu et al, 2002). Nuclear translocation of IRS-1 has also been described in mouse embryo fibroblasts stimulated with IGF-I (Tu et al, 2002;Sun et al, 2003), 32D murine cells (Sciacca et al, 2003), osteoblasts (Seol and Kim, 2003), and hepatocytes (Boylan and Gruppuso, 2002). The mechanism by which IRS-1 is targeted to the nucleus is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic -cells, IR-A regulates insulin gene expression and IR-B does the same with -glucokinase but using different classes of phosphatidylinositol 3-kinase (PI3K) (Leibiger et al 2001). In 32D cells, a murine hematopoietic cell line, IR-A sends mitogenic, antiapoptotic signals in response to insulin-like growth factor-II, whereas IR-B is more effective in inducing differentiation (Sciacca et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…The experiments in Fig. 1 were done on cells 48 hours after shifting from IL-3 to the respective ligands (IGF-I for the IGF-IR and insulin for the InR), when the cells are still proliferating (19,20). Not surprisingly, the difference disappears when the cells are shifted to the wrong ligand (i.e., InR/…”
Section: Resultsmentioning
confidence: 99%
“…We used three 32D-derived cell lines for these studies: 32D IGF-IR cells that do not express IRS-1, 32D IGF-IR/IRS-1 cells, and 32D InR/IRS-1, described in detail in previous articles (19,20). 32D InR cells not expressing IRS-1 could not be included in these experiments as they die rapidly (within 16 hours) when shifted to insulin.…”
Section: Introductionmentioning
confidence: 99%